Trajectory Tracking of a Reconfigurable Multirotor Using Optimal Robust Sliding Mode Controller - Derrouaoui, Saddam Hocine; Bouzid, Yasser; Guiatni, Mohamed; Belmouhoub, Amina (University of Eloued جامعة الوادي, 2022)
This work aims to design a robust Sliding Mode Controller (SMC) in order to stabilize and follow the desired trajectory of a new reconfigurable multirotor. Due to changeable shape of the studied drone, the designed SMC in this work consists to ensure the robustness in the face of the parameters interaction, and various uncertainties of the system. In order to select the controller optimal parameters of each flight configuration, a Metaheuristic Algorithm based on Particle Swarm Optimization (PSO) is used. Nevertheless, the control architecture of this multirotor is different to the standard one, which makes it a very difficult task. To evaluate the effectiveness of the SMC, a simulation scenario is carried out, where the multirotor geometry is variable depending on the assigned tasks and environment.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Reconfigurable multirotor, Sliding Mode Controller (SMC), Optimization, PSO